Quality of Life in Asthmatic Patients - Pedram Razi SH; Bassampour SH; Kazemnejad A (Tehran University of Medical Sciences, 2007)
Background & Aim: Asthma, as a chronic respiratory disease, is a major health problem worldwide. The quality of life of asthmatic patients is affected by long-term treatment and continuous episodes of asthmatic attacks. The aim of this study is to assess the quality of life in asthmatic patients.Methods & Materials: This descriptive study carried out among randomly selected asthmatic patients (n=386) referred to lung clinic in Imam Khomeini hospital, Tehran. Data were collected using a two-section questionnaire. The first section was to assess demographic characteristics of the subjects and the second section was to assess the quality of life. Validity of the questionnaire was evaluated using content validity and reliability was determined using a-kronbach.Results: The results showed that the majority of subjects were female, married, illiterate, and in the 41-50 age group. 45.1 per cent of study subjects had relatively appropriate quality of life. Quality of life in 45.3 per cent of the patients was inappropriate. There were significant statistical relationship between sex, age, education, economic status and quality of life (P<0.05).Conclusion: According to the findings, in general, quality of life was inappropriate and relatively appropriate. So comprehensive programs for treatment and care of these patients should be planned.